503 Late-Breaking: Using Random Regression Models to Estimate Genetic Parameters for Milk Production Traits under Different Levels of Heat Stress in Canadian Holstein Cattle. (8th October 2021) - Campos, Ivan; Baes, Christine F; Chud, Tatiane; Cánovas, Angela; Oliveira, Hinayah R; Schenkel, Flavio S
Abstract: Genetically selecting animals that are heat tolerant can help to maintain production efficiency of the dairy industry under thermal challenges. During the summer months in Canada, dairy cows could be under thermal stress. For instance, in Ontario, cows are expected to be 105 days under thermal stress. The objective of this study was to estimate genetic parameters for milk production traits under heat stress in Canadian Holstein cows. A total of 604, 050 test-day records for milk, fat, and protein yields from 78, 516 first-lactation Holstein cows were used in this study. The production data was combined with daily maximum temperature-humidity index (THI; ranging from 30 to 83) calculated based on meteorological records from public weather stations. In total, 58 weather stations were located within a maximum distance of 20 km from each of the 1, 284 herds included in this study. Single-trait random regressions on THI, fitting linear splines to describe the random additive genetic and permanent environmental effects, were used in the genetic analyses. Based on preliminary analyses, the knots of the spline functions were set to THI = 70, 57, and 58 for milk, fat, and protein yields, respectively. Therefore, the models assumed a linear effect of heat stress beyond the THI threshold, allowing to estimate the additive genetic effect under thermal comfort and at different levels of heat stress. The genetic correlations estimated between thermal comfort and heat stress were -0.09, -0.33, and -0.21 for milk, fat, and protein yields, respectively. This indicates an antagonistic relationship between level of production and heat tolerance. However, small differences in heritability estimates were observed above the THI thresholds (they ranged from 0.20 to 0.22 for milk, 0.18 to 0.15 for fat, and 0.14 to 0.15 for protein yields). This study demonstrates the possibility of genetically selecting for more heat-tolerant animals in Canada.